A near-infrared VISTA of the Small Magellanic Cloud. Issue Volume 14:Issue S344(2019) (August 2018) - Cioni, Maria-Rosa L.; Niederhofer, Florian; Rubele, Stefano; Sun, Ning-Chen
Abstract: VISTA observed the Small Magellanic Cloud (SMC), as part of the VISTA survey of the Magellanic Clouds system (VMC), for six years (2010–2016). The acquired multi-epoch YJK s images have allowed us to probe the stellar populations to an exceptional level of detail across an unprecedented wide area in the near-infrared. This contribution highlights the most recent VMC results obtained on the SMC focusing, in particular, on the clustering of young stellar populations, on the proper motion of stars in the main body of the galaxy and on the spatial distribution of the star formation history.